2010
DOI: 10.1007/s00011-010-0250-0
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of substance P with tumor necrosis factor-α in the lymphocytes and mast cells in gastritis in experimental rats

Abstract: SP release from nerve fibers, lymphocytes and mast cells together with TNF-α can enhance the development of gastric inflammation and participate in tissue damage in gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
3
0
3
Order By: Relevance
“…The topographical distribution map will facilitate the study of the functions of SP‐IR axons in the different regions of the stomach. It has been shown that capsaicin‐sensitive afferent axons (SP‐ and CGRP‐containing axons) may be either protective or harmful to the stomach during injuries and diseases (Gazzieri et al., 2007; Harrison & Geppetti, 2001; Larauche et al., 2004; Pongor et al., 2011; Uchida et al., 1993). The detailed analysis of SP‐IR axons in different regions provides a foundation for a quantitative assessment of the changes of SP‐axons in response to noxious stimuli during injuries and in pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The topographical distribution map will facilitate the study of the functions of SP‐IR axons in the different regions of the stomach. It has been shown that capsaicin‐sensitive afferent axons (SP‐ and CGRP‐containing axons) may be either protective or harmful to the stomach during injuries and diseases (Gazzieri et al., 2007; Harrison & Geppetti, 2001; Larauche et al., 2004; Pongor et al., 2011; Uchida et al., 1993). The detailed analysis of SP‐IR axons in different regions provides a foundation for a quantitative assessment of the changes of SP‐axons in response to noxious stimuli during injuries and in pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…xinnal indukált diabetes mellitus) a neuropeptid-tartalmú idegrostok száma szignifikánsan megemelkedett [2,15,18,19]. A varicosus idegrostok sűrű hálózatot alkotnak a hám alatt, a Lieberkühn-kripták között, valamint a gyomor mirigyei között.…”
Section: Saját Kutatási Eredményeinkunclassified
“…A varicosus idegrostok sűrű hálózatot alkotnak a hám alatt, a Lieberkühn-kripták között, valamint a gyomor mirigyei között. A kontrollállatokban a lymphocyták száma 4,7 ± 2,5/1000 μm 2 Korábbi vizsgálatainkban immunhisztokémiai vizsgálattal, konfokális lézermikroszkópiával és elektronmikroszkópos vizsgálatokkal SP-, VIP-és NPY-pozitív immunsejteket mutattunk ki különböző emésztőrendszeri gyulladásokban [16,19,20]. Egyes SP-immunreaktív lymphocyták és hízósejtek szintén immunreaktivitást mutattak TNFα-ra és NFκB-ra is (5. ábra), ami bizonyít-…”
Section: Saját Kutatási Eredményeinkunclassified
“…Az irodalmi adatok alapján ismeretes, hogy számos immunsejt (aktiválódott lymphocyta, makrofág) is képes különböző körülmények (gyulladás és sérülés) alkalmá-val neuropeptideket termelni és ugyanazon peptidreceptorokat is expresszálni [16,20]. Az aktivált immunsejtekből felszabadult neuropeptidek együtt hatva fokozhatják a gyulladást, visszahathatnak a termelődésük helyére és fokozhatják az idegrostokból felszabaduló neuropeptidek hatását is.…”
Section: Megbeszélés éS Következtetésekunclassified